What Students Really Need: Instructional Strategies That Enhance Higher Order Thinking Skills (Hots) Among Unimas Undergraduates - Jerome, Collin; Julia Ai Cheng, Lee; Ting, Su Hie (Universiti Malaysia Sarawak, (UNIMAS), 2017)
The present paper aims to examine one of the challenges in the teaching of HOTS at undergraduate level, that is, the instructional strategies undergraduates genuinely need to enhance HOTS. To achieve this, the paper discusses findings from a study that investigated HOTS among undergraduates at Universiti Malaysia Sarawak (UNIMAS). Self-reported survey and interviews were used to gather the views of 120 undergraduates on HOTS and the teaching of HOTS in tertiary context. The views were then used to develop instructional strategies that could enhance HOTS among UNIMAS undergraduates. The findings show that UNIMAS undergraduates viewed HOTS as those that include critical, logical, reflective, metacognitive, and creative thinking skills. The undergraduates reported that the use of problem-based learning, case-based scenarios, demonstrations, lectures, and discussions were some of the instructional strategies used by their lecturers to enhance HOTS. The findings also show the subject taught, the learning tasks, and the approach(es) taken by the lecturers are some of the factors that may affect the types of instructional strategies that undergraduates really need to enhance their HOTS.